O interpretacji etnicznej wczesnośredniowiecznych pochówków elitarnych. Skandynawowie w państwie pierwszych Piastów i na Pomorzu? - Sikora, Jerzy (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
This paper discusses two groups of early medieval burials associated with the elites of the Piast state and Pomeranian duchies: chamber graves and graves with stone constructions. Features associated with the first group appear in the Piast state and in Eastern Pomerania in the fourth quarter of the 10th century, while in Western Pomerania in the second half of the 11th and in the 12th centuries. Some, especially dating from the 10th and 11th centuries, were interpreted by Polish archaeologists as material traces of the migration of Scandinavians. A similar interpretation was also presented with reference to the graves with stone constructions, known mainly from the areas of Mazovia, Podlasie and Central Poland, where they appeared from the turn of the 10th and 11th centuries, but mainly from the second quarter of the 11th century. Previously, these graves were considered typical of the ethnic Polish (or particularly Mazovian) population. This article is an attempt to critically review these interpretations in the light of an analysis of burials and burial sites, primarily with respect to modern theories of ethnicity and archaeology as a cognitive discipline in the field of ethnic studies. The analysis presented tends to consider at least some of these graves as burials of local elites, and challenges or questions the possibility of their identification as burials of Scandinavians in the current state of research.